2001
DOI: 10.1023/a:1013176129380
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycemic index and glycemic load, and breast cancer risk: A case-control study

Abstract: This study supports the hypothesis of moderate, direct associations between glycemic index or glycemic load and breast cancer risk and, consequently, a possible role of hyperinsulinemia/insulin resistance in breast cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(105 citation statements)
references
References 52 publications
6
97
0
2
Order By: Relevance
“…Three epidemiological studies have looked at this and found direct associations for colorectal and breast cancer (Slattery et al, 1997;Franceschi et al, 2001;Augustin et al, 2001).…”
Section: Glycemic Index and Cancermentioning
confidence: 99%
“…Three epidemiological studies have looked at this and found direct associations for colorectal and breast cancer (Slattery et al, 1997;Franceschi et al, 2001;Augustin et al, 2001).…”
Section: Glycemic Index and Cancermentioning
confidence: 99%
“…The relevance is based on fiber hypothesis, suggesting that fiber consumption reduces the rate of nutrient influx from the gastrointestinal track (Jenkins et al 2002). Augustin et al (2001) and Franceschi et al (2001) reported that the risk of breast and colorectal cancer decreases with incorporation of a low GI diet. A low glycemic food helps in body weight regulation.…”
Section: Glycemic Indexmentioning
confidence: 99%
“…Many internationally relevant agencies, like the Food and Agriculture Organization (FAO) 3 , European Association for the Study of Diabetes 6 and National Health and Medical Research Council of Australia 7 have recommended the consumption of low GI foods/diets to improve health. This recommendation is based on the establishment and diffusion of more appropriate methods for determining GI 2,3,8 , including more accurate determination of available carbohydrate content 9 , and the existence of studies that consolidate the importance of consuming low GI diets for preventing and treating diseases such as type 2 diabetes, cardiovascular diseases, obesity and some types of cancer [10][11][12][13] .…”
Section: Gi =mentioning
confidence: 99%